Dual-functional carbon dots–silver@zinc oxide nanocomposite: in vitro evaluation of cellular uptake and induction of apoptosis1. Issue 7 (21st February 2015) - Sachdev, Abhay; Matai, Ishita; Gopinath, P.
<x xml:space="preserve">Abstract</x> We report here the devleopment of novel CDs decorated on a silver–zinc oxide (CD–Ag@ZnO) nanocomposite (NC) consisting of highly fluorescent CDs and Ag@ZnO.